The semiotic of the Islamic blazon - a related analytical study between the Islamic blazon and its publicity message: رغده بنت فيصل بن خضر الدعواني (Al-Academy, 2021)
This study discusses the semiotic of the Islamic blazon - a related analytical study between the Islamic blazon and its visual publicity message. The aim of the current study is to explore the related relationship between the Islamic blazon and its visual publicity message. The sample is contained Five of Islamic blazon in the Mamelukes period which is between 1250 to 1517. The methodology is descriptive-analytical, and the result is that there is a clear relation between the Islamic blazon with its visual publicity message. This study's recommendation is to go towards analyzing the meanings of the cultural legacies of the Islamic civilization, and researching the implicit meanings accompanying these features leads to a deeper understanding and a comprehensive conception of the cultural concepts in that period of time